ANALISIS SISTEM PENGENDALIAN INTERNAL DAN PROSEDUR AKUNTANSI TERHADAP PENGELOLAAN PERSEDIAAN OBAT DAN BAHAN HABIS PAKAI - Ardinsyah, Dedy; Rofingatun, Siti; Simanjuntak, Aaron M. A. (Fakultas Ekonomi, Universitas Cenderawasih, 2019)
The study mainly is to analyze internal control systems and accounting procedures for themanagement of medicines inventory and consumable medicine supplies in Pharmacy Installation ofthe Public Health Office in the Pegunungan Bintang Regency. This study aims particularly inknowing the effect of partial internal control systems and accounting procedures on medicinesupplies and consumable medical supplies, and to examine the effect of simultaneous internalcontrol systems and accounting procedures on medical supplies and consumables medicine suppliesand to identify which factors have a dominant influence on medicine supplies and consumablemedicine supplies in the Pegunungan Bintang Regency at pharmaceutical installation.The research approach was used descriptive, comparative, correlation, survey, ex post facto, theexperiment, quasi-experiment, and single-subject method derive from 43 respondents as samples inthis study. Furthermore, interviews, documentation, and questionnaires were used as datacollection techniques that conducted to test the data collection instrument, then the validity test andreliability test were performed to obtain properness the test results and the consistency of the testresults. Data analysis techniques established in the form of analysis methods, hypothesis testing,and test requirements analysis with the results of the study.The results of the analysis show that Internal Control has a positive and significant influence on theManagement of Medicine Preparations and consumable medicine supplies on PharmacyInstallation Offices of the Public Health Office of Pegunungan Bintang Regency, while AccountingProcedures have a positive and significant effect on the Management of Medicine Preparations andconsumable medicine supplies on Pharmacy Installation Office of Pegunungan Bintang Regency inPublic Health Office, Internal Control and Accounting Procedures simultaneously have a positiveand significant influence on the Management of Medicine Preparations and consumable medicinesupplies on Pharmacy Installation Office of Pegunungan Bintang Regency in Public Health Officetogether raised by one unit, it will improve the Management of Medicine Preparations andconsumable medicine supplies on Pharmacy Installation Office of Pegunungan Bintang Regency inPublic Health Officer and the Accounting Procedure Variables most dominantly affecting theManagement of Medicine Preparations and consumable medicine supplies on PharmacyInstallation Office of Pegunungan Bintang Regency in Public Health Office.